The price of fear al-Qaeda and the truth behind the financial war on terror - Warde, Ibrahim (I.B. Tauris, 2007)
This book traces the origins of the money laundering template and discusses the laws, rules and regulations designed to combat its effectiveness. Warde shows that the tracking of clean money being "soiled" for illicit purposes requires fundamentally different intelligence and law enforcement.